Waste water treatment by iron nanoparticles prepared by pulsed electrochemical deposition - Fazekas Éva; Mátyás-Karácsony Zsuzsanna; Furkó Mónika; International Symposium on Analytical and Environmental Problems (21.) (2015) (Szeged) (2015)
Recent industrial and urban activities have led to elevated concentrations of a wide range of contaminants in groundwater and wastewater, which affect the health of millions of people worldwide. In recent years, the use of zero-valent iron (ZVI) for the treatment of toxic contaminants in groundwater and wastewater has received wide attention and encouraging treatment efficiencies have been documented. In the present work, nanoscale iron was prepared by pulse electrodeposition of nano iron by chemical reduction of iron chloride and iron sulfate. Our research focuses on iron nanoparticles preparation and its use for wastewater treatment.